Guerrilla film scoring : practical advice from Hollywood composers - Borum, Jeremy (Lanham, Maryland : Rowman & Littlefield, 2015)
Borum provides valuable guidance on how to make a good film score both quickly and inexpensively. With insights from professional composers, this handbook encompasses the entire film scoring process including education, preparation, writing and recording a score, editing, mixing and mastering, finding work, career development, and sample contracts.
Introduction: The new scoring landscape -- Preproduction. Education -- Team building -- Before you begin -- Time management -- Production. Writing -- Demos -- Score preparation -- Preparing for sessions -- The studio -- Performing -- Producing -- Postproduction. Music editing -- Mixing and mastering -- Finding work -- Career development -- Musi
Includes index.
Keywords: Motion picture music -- Vocational guidance; Film composers -- Interviews; Interviews